Aristotle (with the help of Plato) against the claim that morality is 'only by convention'. Issue 1 (April 2019) - Brown, Lesley
Abstract : I examine Aristotle's brief remarks in N.E. I.3 to the effect that fine and just things –  ta kala and ta dikaia –  have much diversity and variation ( diaphora kai planē ) and hence are thought to be by convention only, not by nature. He rebuts this by remarking that goods ( ta agatha ) too admit of some variation. I briefly explore the nomos/phusis contrast, and the import of 'diversity and variation', with a glance at the issue of how to understand Aristotle's remarks about adultery, theft and murder (N.E. 1107a8ff). In a further discussion of the 'by convention' thesis (N.E. 5.7) Aristotle argues that what is changeable (i.e. variable according to circumstance) can still be 'by nature', thus rebutting the view that what is by nature must be unvarying. In effect, I argue, Aristotle allows that all just things (e.g. rules of action) vary according to circumstance, but denies that this means they are just 'by convention only'. Helpful to understanding Aristotle's brief argument in 1.3 against the 'by convention only' thesis is Theaetetus 172ab, reprised at 177cd. At both points Socrates insists that even if just things are held to depend on a city's conventions, no-one would have the face to say the same about what's good, i.e. beneficial. The relation between the fine and the just, on the one hand, and the good in the sense of the beneficial, on the other hand, is the key to how (in their different ways) Plato and Aristotle answer the view that morality is 'by convention only'. See also Republic VI, 505a and 505d.